KONDISI SOSIAL EKONOMI DAN KESEJAHTERAAN PETANI DI PERUMAHAN PENGUNGSI KELURAHAN PANDU KECAMATAN BUNAKEN KOTA MANADO - Virjinia ., Pangkey; Charles R. Ngangi; Paulus Adrian Pangemanan (Sam Ratulangi University, 2018)
This study aims to determine the social and economic conditions in the Village Pandu Bunaken District Manado city. This research was carried out in Pandu Village, Bunaken District, Manado city for 3 months starting from Juny until August 2017 starting from preparation, taking data to preparing research report. Data collection methods in this study using primary data and secondary data. Primary data obtained directly from the source by using questionnaires to 30 farmers respondents who domiciled the research area, while secondary data was obtained from institutions related to the research of the village government Pandu. The results showed that the socio-economic conditions and welfare of farmers in refugee housing belong to category of low level of welfare.